Evaluating the impact of the alcohol act on off‐trade alcohol sales: a natural experiment in Scotland. (12th September 2014) - Robinson, Mark; Geue, Claudia; Lewsey, James; Mackay, Daniel; McCartney, Gerry; Curnock, Esther; Beeston, Clare
Abstract Background and Aims A ban on multi‐buy discounts of off‐trade alcohol was introduced as part of the Alcohol Act in Scotland in October 2011. The aim of this study was to assess the impact of this legislation on alcohol sales, which provide the best indicator of population consumption. Design, Setting and Participants Interrupted time–series regression was used to assess the impact of the Alcohol Act on alcohol sales among off‐trade retailers in Scotland. Models accounted for underlying seasonal and secular trends and were adjusted for disposable income, alcohol prices and substitution effects. Data for off‐trade retailers in England and Wales combined (EW) provided a control group. Measurements Weekly data on the volume of pure alcohol sold by off‐trade retailers in Scotland and EW between January 2009 and September 2012. Findings The introduction of the legislation was associated with a 2.6% (95% CI = −5.3 to 0.2%, P = 0.07) decrease in off‐trade alcohol sales in Scotland, but not in EW (−0.5%, 95% CI = −4.6 to 3.9%, P = 0.83). A statistically significant reduction was observed in Scotland when EW sales were adjusted for in the analysis (−1.7%, 95% CI = −3.1 to −0.3%, P = 0.02). The decline in Scotland was driven by reduced off‐trade sales of wine (−4.0%, 95% CI = −5.4 to −2.6%, P < 0.001) and pre‐mixed beverages (−8.5%, 95% CI = −12.7 to −4.1%, P < 0.001). There were no associated changes in other drink types in Scotland, or in sales of any drink type in EW. Conclusions The introduction of the Alcohol Act in Scotland in 2011 was associated with a decrease in total off‐trade alcohol sales in Scotland, largely driven by reduced off‐trade wine sales.